Composition System in the experience of the artist Georges Braque - Bedn, Ritaj Ibrahim (Research Journal in Advanced Humanities, 2024)
Our research deals ( Composition System in the experience of the artist Georges Braque) addresses Based on the importance of research as an effective energy, the diversity of material and experimentation carried out by the artist George Braque , through his transitional phases in his constructive system between analysis and composition in his artistic output. In its methodological frameworks Chapter I highlighted the problem of research and its importance and came up with several questions for the problem: What constructive composition system is followed by the artist in his achievements for his artistic experience? What techniques and mechanisms do I adopt in shaping his artistic achievement? Influential or associated references in George Braque artistic experience that contributed to the creation of those intellectual variables or theses through his transition stages within the artistic achievement? Is the artist’s experience, an extension or a reference for many contemporary art products, which we are witnessing today in the arena of art formation?.